THE EFFECT OF TEMPERATURE DIFFERENCES ON HATCHING RATES OF LEKANG TURTLE (Lepidochelys olivacea) EGGS IN SEMI-NATURAL NESTS - Ginting, Daniel Paskah; Nasution, Syafruddin; Siregar, Yusni Ikhwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This research was conducted on August 31, 2021 – December 7, 2021, at the UPTD KPSDKP, West Sumatra Province. The purpose of this study was to determine the effect of temperature differences on incubation time, hatching rate, and survival rate of turtle hatchlings (Lepidochelys olivacea). The method used in this study is an experiment that uses 3 trials plus 1 control, with 3 repetitions. Turtle eggs were incubated with the same depth and number of eggs with the addition of different temperatures from incandescent lamps with different powers. Then proceed with the calculation of incubation time, percentage of hatching, and survival of hatchling. Based on the results of the research, for the calculation of incubation time, the experimental unit with the shortest incubation period was produced by experimental unit B, with a temperature range of 27.5–29.5⁰C, which was 58 days. The incubation period that took the longest was the control experimental unit with an average temperature of 25⁰C, which was 65 days. For the results, the most optimal hatching rate was produced by experimental unit B, with an average hatching rate of 86%. Meanwhile, the lowest hatching rate was obtained from experimental unit C with an average hatching rate of only 53.3%. Then for the survival of the hatchlings after being quarantined for one week, all of them show the number 100%, which means that no hatchlings died during the quarantine.